2018
DOI: 10.2138/am-2018-6489
|View full text |Cite
|
Sign up to set email alerts
|

Questioning the biogenicity of Neoproterozoic superheavy pyrite by SIMS

Abstract: The Neoproterozoic sulfur isotope (δ 34 S) record is characterized by anomalously high δ 34 S pyrite values. Many δ 34 S pyrite values are higher than the contemporaneous δ 34 S sulfate (i.e., δ 34 S pyrite > δ 34 S sulfate ), showing reversed fractionation. This phenomenon has been reported from the Neoproterozoic post-glacial strata globally and is called "Neoproterozoic superheavy pyrite." The commonly assumed biogenic genesis of superheavy pyrite conflicts with current understanding of the marine sulfur cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 201 publications
(290 reference statements)
0
46
1
Order By: Relevance
“…During diagenesis, the system became anoxic and framboidal pyrite formed through bacterial sulfate reduction (BSR) in the sulfate reduction zone. Although the pyrite framboids in the DFMnD range from 10 to 30 μm in size, previous research has revealed that the pyrite framboids in the DFMnD witnessed thermochemical sulfate reduction (TSR) and contain growth rims with superheavy δ 34 Spyrite (+50‰ to +70‰) and normal cores with biogenic δ 34 Spyrite values (+15‰ to +20‰) (Cui et al, 2018). The original diameters of the pyrite framboids in the DFMnD should have been 2-5 μm.…”
Section: Post-burial Diagenesis Of the Mn Ore Depositsmentioning
confidence: 99%
“…During diagenesis, the system became anoxic and framboidal pyrite formed through bacterial sulfate reduction (BSR) in the sulfate reduction zone. Although the pyrite framboids in the DFMnD range from 10 to 30 μm in size, previous research has revealed that the pyrite framboids in the DFMnD witnessed thermochemical sulfate reduction (TSR) and contain growth rims with superheavy δ 34 Spyrite (+50‰ to +70‰) and normal cores with biogenic δ 34 Spyrite values (+15‰ to +20‰) (Cui et al, 2018). The original diameters of the pyrite framboids in the DFMnD should have been 2-5 μm.…”
Section: Post-burial Diagenesis Of the Mn Ore Depositsmentioning
confidence: 99%
“…δ SCRS values can reflect variable contributions by multiple generations of mineral growth (Cui et al, 2018) and can be further complicated by the presence of multiple mineralogies (e.g., pyrite and marcasite; Bryant et al, 2019). Sulfide minerals record an integrated value representing the  34 S of aqueous sulfide during their formation.…”
Section: Introductionmentioning
confidence: 99%
“…First, by rastering over grains, scanning ion imaging can generate a continuous record of isotope variations, one that can be interrogated at variable spatial resolution after data collection. Previously, most SIMS studies of pyrites relied on analyses of fairly large (≥10 μm‐diameter) spots within grains . This precludes analyses of many sedimentary pyrites (i.e., those with diameters <10 μm).…”
Section: Introductionmentioning
confidence: 99%
“…Progress has been made using spot analyses by secondary ion mass spectrometry (SIMS) 1,23,[28][29][30][31][32][33][34][35][36][37][38] or laser ablation (LA)-MC-ICP-MS, 20,39,40 to make spatially resolved δ 34 S measurements. Some have already attributed detectable intra-sample pyrite δ 34 S variability to temporal changes in the S-isotopic composition of the fluids from which the pyrites precipitated.…”
mentioning
confidence: 99%
See 1 more Smart Citation